ANALISIS PENGARUH PRICE EARNING RATIO (PER), CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER) DAN TOTAL ASSET TURN OVER (TATO) TERHADAP RETURN ON ASSETS (ROA) PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2010 - 2012. - Dewi Oktary (STIE 'INDONESIA' Pontianak, 2016)
This study aims to find empirical evidence of the influence of financial ratios such as Price Earning Ratio (PER), Debt to Equity Ratio (DER), the Current Ratio (CR), Total Asset Turn Over (TATO) on Return on Assets of banking companies on the Indonesian Stock Exchanges. Objects taken were 18 banking sector issuers listed on the Indonesia Stock Exchange with the research methods between 2010 and 2012. The analytical method used is Multiple Linear Regression (Multiple Linear Regression). By using multiple regression analysis, the results showed that the variables simultaneously PER, DER, CR and TATO significant influence on ROA value of determination coefficient of the regression model this study was 37.9%. These values show that 37.9% ROA dependent variable that can be explained by the independent variables PER, DER, CR, TATO 63.1% while the dependent variable is explained by other factors not included in the regression model